Clinical Significance of Early Detection of Esophageal Cancer in Patients with Head and Neck Cancer - Lim, Hyun; Kim, Do Hoon; Jung, Hwoon-Yong; Gong, Eun Jeong; Ahn, Ji Yong; Kim, Mi-Young; Lee, Jeong Hoon; Choi, Kwi-Sook; Choi, Kee Don; Song, Ho June; Lee, Gin Hyug; Kim, Jin-Ho (Gut and liver, 2015)
The efficacy of surveillance for esopha-geal squamous cell neoplasia (ESCN) in patients with head and neck squamous cell carcinoma (HNSCC) remains contro-versial. Our study aimed to provide clinical data concerning the necessity of surveillance for detecting early ESCN in pa-tients with HNSCC. We retrospectively reviewed the data from 714 patients who were pathologically confirmed as having HNSCC (n=236 oral cavity cancers, 137 oropha-ryngeal cancers, 87 hypopharyngeal cancers, and 254 la-ryngeal cancers). Of 714 patients, during a median follow-up of 31 months, 48 ESCNs (37 synchronous and 11 metachronous) were detected in 36 patients (5%). Fifteen synchronous lesions (40.3%) were early ESCN, whereas nine metachronous lesions (81.8%) were early ESCN. The 3-year survival rates of HNSCC only and HNSCC combined with ESCN were 71.2% and 48.2%, respectively (p<0.001). Among 36 patients with ESCN, the 3-year survival rates for early and advanced ESCN were 77.7% and 21.7%, respec-tively (p=0.01). In the multivariate analysis, alcohol consump-tion and hypopharyngeal cancer were significant factors associated with the development of ESCN. HN-SCC patients with early ESCN were similar in prognosis with patients without ESCN, in contrast to patients with advanced ESCN. Therefore, surveillance for the early detection of ESCN in patients with HNSCC, especially in alcohol drinkers and those with hypopharyngeal cancer, is warranted. (Gut Liver, 2015;9159-166).